Pengaruh penggunaan media animasi terhadap hasil belajar siswa pada materi pencernaan manusia kelas V sekolah dasar - Melani Amalia (COLLASE (Creative of Learning Students Elementary Education), 2023)
Learning in education needs to be improved again, one of which is by using more fun learning media. In learning science in elementary schools, it is necessary to have media that is fun and better understood by students so that the material delivered is better. One of the media that can be used in science learning is animation media. This media can attract students' attention with visual audio. Animation media in science learning can be applied to the digestive system material in humans. With real impressions shown in the form of digestive videos that start from the mouth to the anus. With the animation media used in science learning, it is expected that students can improve significant learning outcomes. In this study using a quasi-experimental method or also called a quasi-experimental which is a type of quantitative method. The subjects in this study were fifth grade students at SDN 1 Sukamanah. The population in this study were 40 students. The instruments used in this study were multiple choice questions. This research was conducted to determine between the experimental class and the control class with the treatment used. So that there is influence or not the animation media. The research results show an increase in learning outcomes with the use of animated media.